Evaluation of skull and mandible morphometric measurements and three-dimensional modelling of computed tomographic images of porcupine (Hystrix cristata) - Baygeldi, Saime Betul; Guzel, Baris Can; Kanmaz, Yesim Aslan; Yilmaz, Sadik (Wiley, 2022)
Although there have been morphological and morphometric studies on the porcupine skull, three-dimensional modelling of the skull is performed for the first time with the present study. In this study, it was aimed to model the skull and mandible of Hystrix cristata in 3D to reveal its morphometric values and the differences between the sexes. Morphometric analyses were performed on a total of eight (four male and four female) adult porcupine skulls and mandibles. Skulls and mandibles of porcupines were scanned usinf a 64-detector MDCT (General Electric Revolution) device at 80 kV, 200 MA, 639 mGY and 0.625 mm slice thickness. Skull and mandible reconstructions were made with the help of MIMICS 20.1 (Materialize) software program and the surface area and volume values of the skull and mandible were calculated. Statistical analyses were carried out using SPSS 22.0 software. The longest measurement in the skulls, based on the metric measurement points, was the total length (TL), and it was measured as 135.4750 +/- 0.54976 mm in males and 134.4725 +/- 0.86681 mm in females (p < 0.5). The highest value was the foramen magnum index (p < 0.5), and the lowest value the was skull index (p < 0.1). While the total volume ratio of the mandibles was 29901.64 mm3 in males, it was 27296.20 mm3 in females (p > 0.5). Statistical differences in the morphometric values of skulls and mandibles of male and female porcupines were demonstrated for the first time using CT and three-dimensional modelling software.
Keywords: 3D modelling; morphometry; porcupine; skull